Genitive case in Turkish - Kuzgun, Aslı. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis explores the syntactic contexts with a genitive case in Turkish. The genitive case in Turkish occurs with the pronominal complements of a set of postpositions, on possessors and the subjects of embedded clauses. The genitive case with postpositions differs from the genitive case in other positions and is identified as a lexical case due to being idiosyncratic. The distinctive allomorphy patterns of the lexical genitive case presented in this thesis point to a further division between the two contexts. Considering the syntactic and behavioral differences between the lexical and the structural genitive case, it is claimed that the genitive case with postpositions is a different case from the genitive case in other positions. The genitive case on possessors and the subjects of embedded clauses are analyzed as an unmarked case in Turkish. It is argued that the structural genitive case can only occur at Spec, DP. Following this argument, the subject case alternation in the embedded clauses is discussed. It is observed that the embedded clauses occur with nominative subjects when they combine with certain postpositions. Building on this observation, it is suggested that the embedded clauses are headed by Ds, which differ in their phrasal properties, and that the postpositions select the type of D they combine with. Overall, this thesis defines two kinds of genitive cases in Turkish and discusses the morphosyntactic conditions for realizing each.
Keywords: Turkish language -- Case.; Turkish language -- Morphosyntax.